Kaji Eksperimen Terhadap Penggunaan Bahan Bakar Emulsi Pada Burner - Sarjono Sarjono (Politeknik Negeri Padang, 2021)
The purpose of this study was to observe the combustion of diesel fuel combined with the percentage volume of water and emulsifier, namely alkyl benzene sulfonic acid (ABS). The emulsion fuel composition used in this experimental study is a mixture of diesel fuel, emulsion and water. The composition of the emulsion fuel is designed according to the percentage of water volume and the emulsifier in diesel fuel with a variation of the percentage of 10%, 20%, and 30%. The parameters observed were combustion flame temperature, combustor annulus wall temperature, hot gas temperature, air fuel ratio (AFR), heat loss, and flame shape from differences in the composition of the percentage volume of emulsion fuel. In this test using Combustion Laboratory Unit C 491. The results showed that the heat absorbed due to cooling (Qa) in the AFR stoichiometry of diesel fuel (diesel) 26.334 kW was smaller than emulsion fuel (30.096 kW), so the use of emulsion fuel on the Burner Combustion Laboratory Unit C 49 is very suitable. The shape of the flame produced by the combustion of emulsion fuel is short, turbulent, and covered in water vapor.